(untitled) (Journal of Educational Sciences, 2016)
In the article volunteering is considered as technology education, based on the development of many humanistic qualities, on the promotion of civil-Patriotic formation of the person. Analysis of socially useful activity of students, as the beginning of formation of the volunteer movement in the al-Farabi Kazakh national University at the Student scientific society «LOGOS». The author refers to some items that govern the process of formation of the volunteer movement. The author proves the necessity of creation of a complex of pedagogical conditions, giving volunteering «life nature». Noting that the student environment encompasses the vast potential of the creative intellectual energy, willingness to socially active positive activity, the author recognizes as fundamental conditions of formation of the volunteer movement – cultivation ideas of altruism (and supported as an example, used the older mentors). Social-psychological direction in volunteer activities of the Student scientific society «LOGOS» is recognized as a priority. It is noted that this direction is represented by the system of correctionaldeveloping, personal-reflective exercises and different types of games that are connected in mini-training, which is aimed at establishing a system of attitudes, strengthening social position, personal development and leadership school students and students of 1 course. The author also highlights the outreach activity volunteers of SSS «LOGOS», which presents the organization and conduct outreach and popular education activities, devoted to the problems of science, education, culture, ecology and health in schools, children’s homes, special boarding schools, homes for the elderly and other social and educational institutions. This focuses on the fact that in the framework of this direction the students develop social projects. By implementing such projects as «We are for Life!» and «Who, if not we!» it is proved demand in the society of humanistic and altruistic ideas. In the end, the author notes that thanks to the volunteer activity of SSS «LOGOS» students learned to analyze and identify the nature and causes of social problems of the population, to focus in the areas of social state policy conducted in the country, acquired responsibility for professional training, hard work and unselfishness.